EXPLORING THE CONCEPT OF UBUNTU IN RELATION TO DYING WITH DIGNITY IN PALLIATIVE AND HOSPICE CARE - Ntokozo Mnyandu (Obiter, 2018)
The Supreme Court of Appeal in Minister of Justice and Correctional Services v Estate Stransham-Ford raised more questions than the answers it provided. However, of note is the enquiry it made regarding the implications of palliative care in relation to whether the criminality of physician-assisted suicide and physician- administered euthanasia infringes a person’s dignity. In response, this paper aims to reconstruct – through the lens of Ubuntu – our understanding of human dignity and draw links with how the values of compassion and survival, which underpin Ubuntu, enjoin us as a re-affirmation of human dignity, to strive towards making hospice and palliative care readily available. Ultimately, this is done for the benefit of providing constitutionally sound reasons for why greater emphasis should be placed on palliative and hospice care when it comes to dying with dignity. To this effect, a conceptual framework of human dignity that is based on Ubuntu is summarised. This is done for the purpose of properly aligning the understanding of the right to dignity to one that represents our constitutional dispensation and ethos. Flowing from this is an extract of the values of compassion and survival that underpin Ubuntu. These values are then used to gain a lucid perspective, as to why – in our pursuit of providing a dignified death for terminally ill patients – greater emphasis should be placed on hospice and palliative care.